Aims and tasks of the project “Formation of bank of electronic documents in distance learning of higher pedagogical education” (Journal of Information Technologies in Education (ITE), 2009)
The article deals with the experience of the staff of Kherson State University Research Institute of Information Technologies in implementation of scientific and technical work within the framework of the government program «Information and communication technologies in education and science», according to the agreement № ІТ/583-2009 from 23.10.2009. As the result a web-resource of a bank of electronic documents in distance learning of higher pedagogical education will be formed.
Keywords: bank of electronic documents; distance course; distance learning; higher pedagogical education; questionnaire